RADD DALAM HUKUM KEWARISAN DI TUNISIA (Mazahib, 2007)
According to etymology, radd means to return. In its terminology, radd is returning what remain from the deceased property to dzawil furudh nasabiyah pursuant to their portion if there is no other heirs entitled to receive the property. According to Maliki’s school of law, radd cannot be returned to dzawil furudh nasabiyah; it should be given to baitul mal (Islamic treasury), instead. Tunisia which adopts Maliki’s school of law, interestingly, promulgate a somewhat different concept of radd in its family law. This article therefore is to discuss this inconsistency.